2006
DOI: 10.1007/11881216_33
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Conformant Planning into SAT Through Compilation and Projection

Abstract: Abstract. Conformant planning is a variation of classical AI planning where the initial state is partially known and actions can have nondeterministic effects. While a classical plan must achieve the goal from a given initial state using deterministic actions, a conformant plan must achieve the goal in the presence of uncertainty in the initial state and action effects. Conformant planning is computationally harder than classical planning, and unlike classical planning, cannot be reduced polynomially to SAT (u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…2003) is similar to dlv K in identifying a potential plan before validating it. compile-project-sat (Palacios and Geffner 2005) uses a single call to a SAT solver to compute a conformant plan. Their validity check is doable in linear time, if the planning problem is encoded in deterministic decomposable negation normal form.…”
Section: Methodsmentioning
confidence: 99%
“…2003) is similar to dlv K in identifying a potential plan before validating it. compile-project-sat (Palacios and Geffner 2005) uses a single call to a SAT solver to compute a conformant plan. Their validity check is doable in linear time, if the planning problem is encoded in deterministic decomposable negation normal form.…”
Section: Methodsmentioning
confidence: 99%
“…As shown in Fig.1, CGP [5] is a modification of Graphplan [20], which enjoys great success in classical planning field. References [27,36] have shown that conformant planning can be compiled into SAT instances and thus be solved by efficient SAT-solvers. Similar ideas can be found in the famous classical planning systems like SATPLAN [37][38][39] and BlackBox [40].…”
Section: Related Workmentioning
confidence: 99%
“…Cf2sat is an optimal conformant planner presented by Palacios and Geffner [27]. Cf2sat transforms the PDDL into a propositional theory, that is later compiled into normal form called Decomposability and Determinism of Negation Normal Form (d-DNNF) [28][29][30][31] to obtain a new formula that encodes all the possible plans.…”
Section: H Cf2sat and Cf2csmentioning
confidence: 99%
“…There are also approaches that resolve a conflict by extending the instance by clauses that contain auxiliary variables new in the instance by lazily expanding a corresponding part of a large known encoding of the constraint [3,20]. Specific situations, where a CNF encoding of a DNNF is suitable for use in a SAT instance are described in [29,32].…”
Section: Introductionmentioning
confidence: 99%